Citation Analysis of Library and Information Science Undergraduates’ Projects in Kwara State University, Malete (2013-2018) - Rasaq, Abdullahi Maito; Yusuf, Abdulkadir Olalekan; Nuhu, Silifat Ranti; Ibrahim, Abdullahi Muhammed (Jurusan Ilmu Perpustakaan dan Informasi Islam Universitas Islam Negerin Datokarama Palu, 2024)
Citation analysis of Library and Information Science undergraduates’ research projects in Kwara State University, Malete (2013-2018). The population of the study consists of all the submitted undergraduates’ projects to the Department of Library and Information Science, Kwara State University, Malete from 2013-2018. From this population, a total of thirty-seven (37) final-year students’ projects of the Department were selected as the sample size of the study using the systematic sampling technique. Coding sheet was used to collect data. The frequency counts and simple percentages were used for the statistical analysis. The findings revealed that more than half of the citations in the projects were journal articles, one-third of the citations were conference papers, few of the citations were recent, there were no citations without author, and the highest number is seventy-seven (77) while the lowest citation in a project is eighteen (18). The following recommendations were made based on the findings. Final year students should be encouraged to consider more recent research for their projects, students should be advised cautioned against low citation as eighteen (18) in a research project, the university library should consider the acquisition and subscription to journals so as to aid the research of the students.